2005
DOI: 10.1080/09540120500119940
|View full text |Cite
|
Sign up to set email alerts
|

A situational analysis of HIV/AIDS-related discrimination in Hanoi, Vietnam

Abstract: The laws in Vietnam provide a framework within which one may judge the nature and type of health care-related discrimination to which people living with HIV (PLWHA) are subject. Despite the existence of stringent legislation protecting the rights of PLWHA, this study found that, in practice, PLWHA experienced significant structural discrimination in their daily lives. The discrimination experienced by PLWHA was exacerbated by the fact that, historically, HIV is associated with high-risk, marginalized groups su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…30,31 Based on the UNAIDS Protocol for the Identification of Discrimination against People Living with HIV, several studies from the Asia-Pacific region revealed that most instances of discrimination appeared in practice rather than in legislation or written policy. [32][33][34][35] Some studies have examined the linkage between discrimination and work environment in health care settings. In one study, a higher level of nurses' satisfaction with work and work environment was associated with fewer negative verbal mannerisms toward patients with AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Based on the UNAIDS Protocol for the Identification of Discrimination against People Living with HIV, several studies from the Asia-Pacific region revealed that most instances of discrimination appeared in practice rather than in legislation or written policy. [32][33][34][35] Some studies have examined the linkage between discrimination and work environment in health care settings. In one study, a higher level of nurses' satisfaction with work and work environment was associated with fewer negative verbal mannerisms toward patients with AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam and China, drug users are severely marginalized and suffer discrimination from their own families and their communities (Khoshnood and Weber 2003, Hong et al 2004, Khoat et al 2005. Stigma and discrimination pose major challenges to interventions because many drug users are reluctant to contact and engage with prevention services for fear of being identified, arrested, or mistreated.…”
Section: Background: Status Of Hiv Epidemics Among Idus Worldwide Andmentioning
confidence: 98%
“…The official position of the Vietnam government on HIV stigma was, for instance, quite nuanced (130). Broadly, stigmatising PLWHA was not permitted.…”
Section: Stigmamentioning
confidence: 99%